Atelophyllodes gen. n., a new feather mite genus of the family Proctophyllodidae (Astigmata: Analgoidea) from lyrebirds (Passeriformes: Menuridae) - Mironov, Sergey V.; Proctor, Heather C. (Zootaxa, 2009)
We describe a new feather mite genus Atelophyllodes gen. n. (Proctophyllodidae: Proctophyllodinae) with two new species from lyrebirds (Passeriformes: Menuridae) in Australia: Atelophyllodes menurae sp. n. (type species) from Menura novaehollandiae Latham, 1802, and A. atyeoi sp. n. from M. alberti Bonaparte, 1850. The unique features of Atelophyllodes that differentiate it from all other described genera of the subfamily Proctophyllodinae involve the structure of opisthosomal lobes in males: lobes are short and wide, with three pairs of extensions bearing bases of setae h2, h3 and f2, and lack terminal lamellae on their posterior margins.